Acute pulmonary embolism in COVID-19 related hypercoagulability - Lorenzo, Cerruti; Francesca, Boscaro; Francesco, Poletto; Elena, Campello; Luca, Spiezia; Paolo, Simioni (Journal of thrombosis and thrombolysis, 2020)
Since December 2019, a novel Coronavirus (SARS-CoV-2) was confirmed as the etiologic agent of a worldwide outbreak of a pneumonia that can result in severe respiratory failure. This clinical entity seems to be associated with a marked hypercoagulable state that causes both arterial and venous thromboembolic complications. Therefore, an adequate anti-thrombotic prophylaxis is recommended in hospitalized COVID-19 patients. Although rapidly worsening respiratory symptoms in a patient with SARS-CoV-2 respiratory infection may correlate with worsening pneumonia itself, it may also mask a pulmonary embolism. We report the case of a 50-year-old man affected by SARS-CoV-2 pneumonia, who developed acute pulmonary embolism.